2023
DOI: 10.1186/s12912-023-01230-y
|View full text |Cite
|
Sign up to set email alerts
|

Assistive robotic systems in nursing care: a scoping review

Abstract: Background The use of assistive robotic systems in care is intended to relieve nursing staff. Differentiated and literature-based findings on current application possibilities, technological developments and empirical findings are necessary to enable a goal-oriented and participatory development of assistive robotic systems of care. The aim of this review was to identify assistive robotic systems and their areas of application in nursing settings. Furthermore, an overview of existing social and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, the introduction of robots into nursing should be in an auxiliary role to nurses and not as a complete replacement for them. Categories of utilizing robot systems in nursing are diverse, including information and patient data processing, assistance with patient activities, monitoring, telepresence, communication, safety and navigation [44] . A previous study showed that using a meal assistant robot created a more private and independent eating environment and patients comfortably accepted the robot [45] , while another previous study showed patients positively accepting robots instead of fearing them [46] , which suggests that there could be a gap between robot acceptance by patients as imagined by medical staff and the actual reality.…”
Section: Discussionmentioning
confidence: 99%
“…However, the introduction of robots into nursing should be in an auxiliary role to nurses and not as a complete replacement for them. Categories of utilizing robot systems in nursing are diverse, including information and patient data processing, assistance with patient activities, monitoring, telepresence, communication, safety and navigation [44] . A previous study showed that using a meal assistant robot created a more private and independent eating environment and patients comfortably accepted the robot [45] , while another previous study showed patients positively accepting robots instead of fearing them [46] , which suggests that there could be a gap between robot acceptance by patients as imagined by medical staff and the actual reality.…”
Section: Discussionmentioning
confidence: 99%
“…This scoping review aims to understand the extent and type of evidence in relation to robotics integration in nursing practice. Prior work has focused on investigating assistive robotic systems and their application areas in nursing practice [ 35 ]. Also, some reviews have identified the different tracks in which robots are used in nursing, barriers to implementation, and the outcomes of robots and other automated devices on nurses' activities [ 31 , 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surge in the interest in using nursing robots in health care is because of the technological capacity to strengthen health care delivery and improve quality health outcomes [ 21 ]. Nursing robots can complement nurses' efforts by undertaking repetitive work such as retrieving and delivering supplies, providing ambulation services, medication delivery services, assisting in patient transfers, lifting, and assisting with standardized approaches to care management [ 30 , 35 , 36 ]. In addition, robots can enhance nurses' work by monitoring patients' condition and vital signs and providing patient reminders [ 26 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations